The art of happiness in a troubled world [compact disc, unabridged] - Bstan- dzin-rgya-mtsho, Dalai Lama XIV, 1935- (Random House Audio, 2009)
"Blending common sense and modern psychiatry, The Art of Happiness in a Troubled World applies Buddhist tradition to twenty-first-century struggles in a relevant way. The result is a wise approach to dealing with human problems that is both optimistic and realistic, even in the most challenging times. How can we expect to find happiness and meaning in our lives when the modern world seems such an unhappy place? His Holiness the Dalai Lama has suffered enormously throughout his life, yet he always seems to be smiling and serene. How does he do it? In The Art of Happiness in a Troubled World, Dr. Cutler walks readers through the Dalai Lama's philosophy on how to achieve peace of mind and come to terms with life's inherent suffering. Together, the two examine the roots of many of the problems facing the world and show us how we can approach these calamities in a way that alleviates suffering, and helps us along in our personal quests to be happy. Through stories, meditations, and in-depth conversations, the Dalai Lama teaches readers to identify the cultural influences and ways of thinking that lead to personal unhappiness, making sense of the hardships we face personally, as well as the afflictions suffered by others" -- from publisher's web site.